Complete versus Limited Endoscopic Sinus Surgery for Chronic Rhinosinusitis in Adults with Cystic Fibrosis. (April 2020) - Lee, Daniel J.; Yao, Christopher M. K. L.; Sykes, Jenna; Rizvi, Leena; Tullis, Elizabeth; Lee, John M.
Objective: To examine the effects of the extent of endoscopic sinus surgery (ESS) on pulmonary health, including the pulmonary exacerbations and lung function in patients with cystic fibrosis (CF). Study Design: Retrospective cohort study. Setting: Tertiary health care center. Subjects and Methods: A retrospective review of patients with CF who underwent ESS at St. Michael's Hospital between 1999 and 2016 was performed. Two groups of patients were identified based on the surgical extent: (1) complete (maxillary antrostomy, complete ethmoidectomy, sphenoidotomy, and frontal sinusotomy) and (2) limited (any ESS that involved less than complete). Primary outcomes included the number of pulmonary exacerbations (the use of oral or intravenous [IV] antibiotics), number of hospital admissions and hospital days during a 2-year pre- and postoperative period, and pulmonary function outcomes during a 1-year pre- and postoperative period. Results: There were 70 procedures (30 complete and 40 limited) among 57 patients. Baseline characteristics were similar between the groups. Complete ESS group had a significant reduction in the oral antibiotic use compared to the limited ESS group (median, –1.0 [interquartile range (IQR), –2 to 0] in complete vs 0 [IQR, –1 to 1] in limited, P = .028). There was no difference in the use of IV antibiotics, number and duration of admissions, or rate of lung function change between the 2 groups. Conclusion: Complete ESS may reduce mild forms of pulmonary exacerbations as shown in the decreased use of oral antibiotics. Overall, ESS does not significantly modify pulmonary outcomes in patients with CF.